PEMANFAATAN LIMBAH CANGKANG KERANG HIJAU (PERNA VIRIDIS) SEBAGAI ALTERNATIF ABSORBER PADA DESTILASI AIR LAUT TENAGA SURYA TIPE KOLEKTOR PLAT SINUSOIDAL (Universitas Islam 45 Bekasi, Fakultas Teknik, Jurusan Teknik Mesin, 2023)
The efficiency of destilator absorber full of green mussel shells was 34,67% from the researchvolume of 5L seawater, 28% from the research volume of 3L seawater, 37% from the researchvolume of 2L. The efficiency of destilator absorber ½ of green mussel shells was 31% from theresearch volume of 5L seawater, 27,67% from the research volume of 3L seawater, 32,67% fromthe research volume of 2L. The efficiency of destilator absorber without of green mussel shellswas 17,33% from the research volume of 5L seawater, 14,67% from the research volume of 3Lseawater, 20,67% from the research volume of 2L. Also obtained the percentage of full absorberdestilation of green mussel shells 8,55% from research of 5L seawater volume, 12,12% from theresearch volume of 3L seawater, 26,03% from the research volume of 2L seawater. The percentageof ½ absorber destilation of green mussel shells 7,6% from research of 5L seawater volume, 11,5%from the research volume of 3L seawater, 22,98% from the research volume of 2L seawater. Thepercentage of without absorber destilation of green mussel shells 4,29% from research of 5Lseawater volume, 6,32% from the research volume of 3L seawater, 15,05% from the researchvolume of 2L seawater. And the most optimal result of destilation of seawater volume is 2Labsorber full green mussel shells which is 651 ml.